Effects of different types of physical exercise on executive function of older adults: a scoping review - Cai, Zhidong; Cai, Ruibao; Sen, Li (Frontiers in Psychology, 2024)
Objective This scoping review examined the impact of physical exercise on executive function (EF) in older adults and investigated the moderating effects of exercise types. Methods We systematically searched four electronic databases for randomized controlled trials (RCTs) investigating the effects of exercise on EF, published until November 26, 2023. The proportions of positive and null/negative effects across all studies were calculated. Results In total, 91 studies were included in the analysis. Among these, 27 (29.7%) studies employed aerobic exercise interventions for older adults’ EF, with 19 (70.4%) studies reporting positive effects. Additionally, 18 (19.8%) studies utilized strength exercise interventions for older adults’ EF, with 15 (83.3%) studies demonstrating positive benefits. Furthermore, 32 (35.2%) studies employed coordination exercise interventions for older adults’ EF, with 25 (78.1%) studies showing positive benefits. Similarly, 30 (33%) studies applied mixed exercise interventions for older adults’ EF, with 25 (83.3%) studies indicating positive benefits. Conclusion Overall, all four types of physical exercise enhance EF in older adults, with mixed exercises being the most effective.